Effect of Spirulina Nigrita® on Exercise-Induced Oxidative Stress in Humans: A Breath Analysis Study - Anastasios Krokidas; Katerina Mikedi; Athanasios G. Gakis; Spyridon Methenitis; Tzortzis Nomikos; Magdalini Krokida (Applied Sciences)
In the current work, the non-invasive approach of breath analysis is implemented for the first time in an eccentric exercise protocol that investigated the effect of spirulina supplementation on exercise-induced oxidative stress. We assessed whether volatile alkanes in exhaled breath can serve as alternative biomarkers of oxidative stress. A randomized, double-blinded, placebo-controlled, crossover supplementation study was carried out enrolling 14 participants. The volunteers consumed 42 mg·kg−1 body weight of either Spirulina Nigrita® or maltodextrin, as a placebo, daily for 15 days. Afterward, they followed a damaging eccentric exercise protocol of the upper limbs. Expired breath samples were collected from them just before supplementation (baseline measurement), prior to exercise, and 1 h, 24 h, 48 h, and 72 h after exercise. The samples were analyzed by Gas Chromatography/Mass Spectrometry (GC-MS) coupled with a thermal desorption unit (TDU) to determine the alveolar gradient (AG) of several alkanes, C5–C14, that are known to be related to oxidative stress. Apart from breath analysis, TBARSs were also determined as a crude marker of lipid peroxidation. Two-way repeated measures ANOVA tests were applied to the alkanes’ AGs between the spirulina (SPI) and placebo (PL) groups across time. In the PL group, a trend of increasing almost all alkanes immediately after exercise, with a gradual return to pre-exercise levels up to 72 h later was revealed. A statistically significant time effect was observed for 2-methylhexane, 3-methylhexane, heptane, octane, and undecane. The administration of spirulina appeared to reduce the increases in alkanes after exercise, and a statistically significant attenuation was observed for 2-methylpentane and 2-methylhexane. An examination of TBARSs confirmed that the reduced increases observed in the SPI group were due to changes in lipid peroxidation, while a positive correlation between the iAUC of TBARSs and that of 2-methylhexane and 3-methylhexane was revealed. In conclusion, the analysis of volatile alkanes in exhaled breath may serve as an attractive alternative for assessing redox changes after eccentric exercise compared to traditional blood biomarkers.